(untitled) (GESTIÓN Y TENDENCIAS, 2020)
The article analyzes the total distributive effects of the Global Complementary Tax (IGC) by region, comparing them with the Regional Human Development Index (RHDI), which we use as a proxy for the distributive effect of state spending on health, education, and household income. We also compare COVID-19 fatality data, identifying that in the first phase of the pandemic up to May 2020 the worst-affected regions were generally those with negative gaps between their IGC contribution and the RHDI.